Physicochemical and Organoleptic Properties of Mixed Mulberry (Morus alba) Jam at Different Temperatures and Aloe Vera (Aloe vera) Concentrations - Ramadhani, Amalia; Hartati, Fadjar Kurnia; Rahmiati, Retnani (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to determine the effects of temperature and Aloe vera concentration on the physicochemical and organoleptic properties of mixed mulberry (Morus alba) jam. Jam is a semi-solid fruit and sugar-based product that requires a thickening agent to achieve optimal texture. Aloe vera was selected as a natural thickening alternative due to its polysaccharide content, such as acemannan and glucomannan, which can form gels, replacing expensive and import-dependent commercial pectin. The research employed a quantitative experimental method with a Completely Randomized Design (CRD), involving four treatment combinations of Aloe vera concentration (75 g and 100 g) and cooking temperature (70°C and 85°C). The parameters tested included physicochemical properties such as viscosity, fiber content, and vitamin C levels, along with organoleptic evaluations involving 25 panelists to assess viscosity and taste. Data were analyzed using analysis of variance (ANOVA) and an effectiveness test to identify the best treatment. The results showed that the combination of 100 g Aloe vera concentration and a cooking temperature of 85°C produced the best-quality jam, characterized by optimal viscosity, high fiber content, preserved vitamin C levels, and high panelist preference for viscosity and taste. This conclusion highlights the potential of Aloe vera as a cost-effective and value-added natural thickening agent for the food industry.